Analisis Karakteristik Konsumen dan Faktor Dominan Keberhasilan Promosi UMKM Kab. Subang di Media Sosial - Haryati; Rian Piarna; Nunu Nugraha Purnawan; Dwi Vernanda; Tri Herdiawan Apandi; Nurfitria Khoirunnisa (Bulletin of Information Technology (BIT), 2022)
Promotion is a marketing communication that aims to attract and convince consumers to buy the products or services offered. Social media as a promotional medium with a wider target market reach and relatively low cost. The purpose of the study was to analyze consumer characteristics based on age range, gender, social media used, product category sought, and product criteria. These attributes are then analyzed using the k-means clustering algorithm. In addition, an analysis of the dominant factors that influence the success of promotion through social media is carried out using the Analytical Hierarchy Process (AHP) algorithm. Determination of criteria and sub-criteria through Focus Group Discussion (FGD) with 5 MSME actors and 10 consumers. The results of clustering form 2 clusters with an evaluation of the DBI value of 0.089. Cluster 0 members are 44 respondents and cluster 1 are 26 respondents. The results of data analysis show that Instagram, Facebook, and Whatsapp social media users are dominated by women aged 17-35 years. The most sought after product categories are fast food and product review criteria are reasons for consumers to buy. Furthermore, from the results of the dominant factor analysis using the analytical hierarchy process, five dominant factors that influence the success of promotions on social media are obtained, namely Product Reviews, Quality of Service to Consumers, Quality Content, Influencer Services, and Actively Interacting in Online Community.